Gazing Into the Mirror II : Performance Contracts in Cameroon Customs - Likeng, Minette Libom Li; Djeuwo, Marcellin; Bilangna, Samson (World Bank, Washington, DC, 2014)
This paper revolves around the World Customs Organization's (WCO) 2011 theme of the year, 'knowledge as a catalyst for excellence'. The contracts clearly define the scope and procedures for their implementation. In light of the foregoing, the policy for performance contracts is part of the effort to implement the plan to reform the Customs Administration. These contracts aim to combat customs fraud and corruption more effectively, and introduce speed and efficiency in the processing of files. In other words, the contracts, which are based on objective indicators, seek performance, responsibility, and transparency, with a particular emphasis on ethics. Inspectors who sign the contract must work swiftly, while seeking to uncover fraud. To that end, they must be present at their work stations, behave in a professional manner, and themselves be confident that their contribution to efforts to reduce clearance times and costs of goods is essential. In sum, the procedure seeks to enhance the performance of Cameroon customs with a view to providing quality service to enterprises, improving the effectiveness of controls, and simplifying administrative procedures during border crossings.